Chapter 2 Historical overview of curriculum organisation National control over curriculum vs. school-based curriculum development - Nishioka, Kanae (Taylor & Francis, 2017)
This book provides a comprehensive overview of the history and current status of policy, research and practices of curriculum, classroom instruction and assessment in Japan. It outlines the mechanism of curriculum organization and the history of the National Courses of Study, and assesses the theories of academic ability model. It also discusses in detail the history of "Lesson Study" - a characteristic teaching practice in Japan which utilizes groups, and reviews the history of educational assessment in Japan. Case studies on the practice of portfolio assessment in the Period for Integrated Study, as well as the practice of performance tasks in subject-based education are illustrated to show various examples of teaching practices.